2008
DOI: 10.1038/sj.bjc.6604527
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial stromal sarcoma: a population-based analysis

Abstract: To determine independent prognostic factors for the survival of patients with endometrial stromal sarcoma (ESS), data were abstracted from the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute from 1988 to 2003. Kaplan -Meier and Cox proportional hazards models were used for analyses. Of 831 women diagnosed with ESS, the median age was 52 years (range: 17 -96 years). In total, 59.9% had stage I, 5.1% stage II, 14.9% stage III, and 20.1% had stage IV disease. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 30 publications
5
140
4
3
Order By: Relevance
“…The problem with regard to earlier studies is that the various conditions were aggregated, preventing meaningful analysis of any single variable (6)(7)(8)(9)(10)(11)(12)(13). Further, some recent studies are still using the older classification (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) …”
Section: Discussionmentioning
confidence: 99%
“…The problem with regard to earlier studies is that the various conditions were aggregated, preventing meaningful analysis of any single variable (6)(7)(8)(9)(10)(11)(12)(13). Further, some recent studies are still using the older classification (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) …”
Section: Discussionmentioning
confidence: 99%
“…16 In terms of prognostic significance, a study of 831 endometrial sarcomas from the Surveillance Epidemiology and End Results database reported worse survival in women over 52 years. 24 By far the most reliable prognostic factor in uterine sarcomas is stage. 15,20,22,24 However, the majority of uterine sarcomas in general present at stage I, 16,22,[24][25][26] therefore predicting behavior in low-stage tumors, particular low-grade endometrial stromal sarcoma, remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…24 By far the most reliable prognostic factor in uterine sarcomas is stage. 15,20,22,24 However, the majority of uterine sarcomas in general present at stage I, 16,22,[24][25][26] therefore predicting behavior in low-stage tumors, particular low-grade endometrial stromal sarcoma, remains a challenge. The proportion of stage I tumors in our series was similarly high, constituting 61% of low-grade endometrial stromal sarcomas, 50% of undifferentiated endometrial sarcomas with nuclear uniformity and 29% of the nuclear pleomorphism group.…”
Section: Discussionmentioning
confidence: 99%
“…The most common organ is ovary, although metastases of lung, bone, and bladder have been reported [8]. A study on 831 patients with all stages of ESS has shown that the 5-year disease-specific survival rate is more than 90% [9].…”
Section: Case Presentationmentioning
confidence: 99%
“…In recent research studies, the incidence of lymphnode metastases in ESS is reported to be 9.9% (28/282) or 7% (7/100). [9,11] Progestin or aromatase inhibitors can be considered for adjuvant therapy. However, currently there is no standard for appropriate dose, regimen, or duration of treatment because there are insufficient prospective and retrospective data [12].…”
Section: Case Presentationmentioning
confidence: 99%